General directives of judicial sentencing. Remarks in the context of the Polish Criminal Code - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The present paper was devoted to the issue of general directives of judicial sentencing. Assuming that such a status is held by the indications enumerated under Article 53 § 1 of the Polish Criminal Code i.e., the degree of culpability, the degree of social harm of a criminally prohibited act, individual prevention and general prevention, in the present paper attention was devoted not only to the essence of the mentioned indications of judicial sentencing, but also to their actual role in that process. The performed analyses allowed for formulating a conclusion that extra-legal factors, following from knowledge and experience of the adjudicating body, do not remain without importance.
Keywords: wyrok sądowy; zasady wymiaru kary; wytyczne dotyczące wymiaru sprawiedliwości